THE “ENTIRE PEOPLE OWNERSHIP” REGIME ON LAND AND THE NATURE OF LAND USE RIGHTS IN VIETNAM - Quoc Thai, Luu (International Journal of Scientific Research and Management (IJSRM), 2021)
Since the Constitution 1980, all land in Vietnam has been regulated to be owned by the entire people (Article 19). This issue continues to be affirmed in the Constitution 1992 (Article 17). The current Constitution 2013 continues to declares: “Land, water resources, mineral resources, resources in the sea and airspace, other natural resources and properties invested and managed by the State are public property owned by the entire people and managed by the State representing owners and unified management” (Article 53). Under this regulation, the current Land Law 2013 states that the State is powered to perform ownership rights as representative of the whole people. Therefore, No one other than the state can become the owner of the land. Individuals and organizations only have “land use rights” in accordance with the law. However, they may have the right to transfer this right (and also include the land) to others. This policy has caused certain complications in accessing land and exercising land rights, especially for foreign entities in Vietnam. So, this paper will discuss what is called the land use rights under the specialized ownership regime on land in Vietnam to clarify relevant legal aspects.